1974
DOI: 10.1128/iai.10.4.889-914.1974
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of the Phenomena of Microbial Persistence and Reversion with Bacterial L-Forms in Human Embryonic Kidney Cells

Abstract: A series of experiments was undertaken in which human embryonic kidney (HEK) fibroblasts were infected with either relatively stable or stable L-forms of Streptococcus faecalis. The infected cells were maintained by splitting over long periods (1 to 2 months) while samples were withdrawn for culture and electron microscopic studies. Relatively stable S. faecalis L-forms could be cultured from infected cells only during the first week after infection, although L-form-like material was frequently detected at lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

1976
1976
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…To investigate whether dormant bacteria are present, we thus need culture‐independent methods, of which ultramicroscopic (e.g. Domingue et al ., ; Domingue, , ; Domingue & Woody, ; Ewald, ; Green, Heidger Jr & Domingue, , b ; Mattman, ; Potgieter et al ., ) and molecular sequence‐based methods (Amar et al ., ; Cherkaoui et al ., ; Fernández‐Cruz et al ., ; Gaibani et al ., ; Grif et al ., , b ; C.L. Liu et al ., ; Moriyama et al ., ; NIH HMP Working Group et al ., ; Nikkari et al ., ; Sakka et al ., ; Sato et al ., ; Valencia‐Shelton & Loeffelholz, ; Woyke, Doud & Schulz, ) are by far the most common.…”
Section: Step –1: a Dormant Blood And Tissue Microbiomementioning
confidence: 99%
“…To investigate whether dormant bacteria are present, we thus need culture‐independent methods, of which ultramicroscopic (e.g. Domingue et al ., ; Domingue, , ; Domingue & Woody, ; Ewald, ; Green, Heidger Jr & Domingue, , b ; Mattman, ; Potgieter et al ., ) and molecular sequence‐based methods (Amar et al ., ; Cherkaoui et al ., ; Fernández‐Cruz et al ., ; Gaibani et al ., ; Grif et al ., , b ; C.L. Liu et al ., ; Moriyama et al ., ; NIH HMP Working Group et al ., ; Nikkari et al ., ; Sakka et al ., ; Sato et al ., ; Valencia‐Shelton & Loeffelholz, ; Woyke, Doud & Schulz, ) are by far the most common.…”
Section: Step –1: a Dormant Blood And Tissue Microbiomementioning
confidence: 99%
“…However, the persistence of antigens derived from the L-form were shown in the tissues at 12 weeks postinjection, and the continual rise in antibody titer suggested that the organisms remained in the tissues but could not be cultured in vitro. This same strain was used in a human embryonic cell culture system and could be cultured as an L-form for up to 73 days postinfection (79). As with the stable L-form in cell culture, there was minimal evidence of histopathologic damage caused by this organism.…”
Section: Host-pathogen Interactions With Cwdb In Germfree Animalsmentioning
confidence: 99%
“…Splitting of infected heart cells by scraping, in lieu of trypsin treatment, and the use of multiple refeedings did not result in their recovery. However, human embryonic kidney cells infected with a stable L-form of S. faecalis have been maintained for up to 60 days by splitting cells by scraping with a rubber policeman (8). Also, use of heat-killed b-forms caused some tissue destruction that was reversible only after trypsin treatment.…”
Section: Fig 10mentioning
confidence: 99%